ADALiN – ambiente digital de aprendizagem de línguas - Araujo, Raissa Arruda de (2019)
This dissertation presents the design, development, implementation and evaluation of a "digital environment" for learning natural languages, entitled ADALin. The novelty is that this environment is designed to serve a community of learners, without separating borders, in the sense that they reach different levels of proficiency, using five (5) abilities: reading, writing, speaking, listening, translating. This digital environment allows the use of Digital Learning Structures, created by teachers to be used for individual or collaborative learning with apprentices of different proficiency levels. Each learner's learning path is freely defined by himself. When the learner needs help choosing the next task to be developed, the environment recommends the activities, structured in the respective EDA, that are appropriate to the current level and proficiency of that learner.